Effect of Using Fine Volcanic Ash Instead of Crushed Basalt Filler in Hot Mix Asphalt - Mohammed A. Alsharafi; Abdullah A. Almaswari; Ziyad M. Algaboby (University of Science and Technology, Sana'a, Yemen, 2024)
Numerous studies over the years have demonstrated the significance and impact of filler in influencing the physical and mechanical properties of Hot Mix Asphalts (HMAs). To overcome such issues, as environmentally friendly alternatives, several different materials for construction have been proposed. This led to an investigation into the potential use of fine volcanic ash (FVA) as a hot mix asphalt filler alternative. In order to prepare bituminous concrete mix sample with conventional basalt filler (BF) as control mix. The Marshall Mix design approach was used to calculate the effective bitumen content. A total of 15 bituminous concrete mix specimens with bitumen content of 4%, 4.5%, 5%, 5.5%, and 6% were created, and the optimum asphalt content was 5.24 %. The impacts of five different (FVA) samples with filler contents of 15%, 30%, 45%, and 60% by weight were compared with respect to bituminous concrete performance. The Marshall stability of a total of 30 samples with varying amounts of (FVA) were investigated. The outcomes were compared with a conventional bituminous concrete mixture. The results showed that fine volcanic ash may substitute 30% of the basalt filler at a bitumen content of 5.24%, 13.84 KN Marshall stability value, 4.0% air voids, 74.77% VFB, 2.380 g/cm3 bulk density and 3.54 mm flow. Therefore, the combination of 30% Fine Volcanic Ash by weight of Basalt Filler satisfies the ASTM Specifications, while the remaining VA content satisfies the basic requirements of the ASTM Specifications.